Worldwide magnitude of inguinal hernia: Systematic review and meta-analysis of population-based studies - Abebe, Melese Shenkut; Tareke, Amare Abera; Alem, Addis; Debebe, Wondwossen; Beyene, Altaseb (SAGE open medicine, 2022)
This review pooled the magnitude of inguinal hernia based on the available population-based studies conducted throughout the world. We have searched for population-based articles reporting the magnitude of inguinal hernia on PubMed/Medline, EMBASE, Cochrane library and Google Scholar. Random-effect meta-analysis was carried out to pool the magnitude of inguinal hernia and its proportion between male and female subjects. To determine the presence of between-study heterogeneity, I2 and Cochran’s Q methods were employed. Publication bias was evaluated by the Egger test and visual examination of a funnel plot. All statistical tests were conducted by Stata version 16 software. Ten population-based studies with a total population of 51,304,093 were incorporated to pool the magnitude of inguinal hernia. The pooled prevalence of inguinal hernia was 7.7% (95% confidence interval: 6.06–9.34). Subgroup analysis showed that the highest pooled prevalence of inguinal hernia (12.72%) was observed in Asia, On the contrary, the lowest pooled prevalence emanated from America, 4.73%. The pooled prevalence of inguinal hernia in males is far higher than females. It was, respectively, 9.61% (95% confidence interval: 6.46–12.76) and 1.31% (95% confidence interval: 0.36–2.26) for males and females. The current meta-analysis revealed a higher burden of inguinal hernia. This finding glares the light that giving greater attention to inguinal hernia is required. It is recommended to identify the significant causes of inguinal hernia and design appropriate prevention as well as management strategies.